Examining resilience: the role of creativity-oriented high-performance work practices and role clarity - Aparna, S.M.; Sahney, Sangeeta (Journal of organizational change management, 2022)
PurposeThe paper aims to highlight the understated role of creativity in R&D organizations by exploring the effect of creativity-oriented high-performance work practices (CHPWPs) on resilience. The moderator effect of role clarity (RC) on the association between CHPWPs and resilience is examined.Design/methodology/approachThe study proposes a simple moderation model to understand the relationship, and specifically hierarchical regression analysis (SPSS 22.0) and SPSS PROCESS Macro has been used to test the hypotheses.FindingsFindings revealed that the implementation of CHPWPs would significantly improve resilience. The benefits of CHPWPs on resilience get compromised as the organizations lay stress on higher levels of RC.Practical implicationsIndian R&D organizations must emphasize upon enhancing resilience through a set of CHPWPs. Rather than laying greater stress on RC, these organizations should build a creative climate characterized by experimentation, freedom and a free flow of ideas.Originality/valueThe current study makes a valuable contribution by highlighting the importance of creativity and resilience in organizations. Although conceptual studies highlight the importance of creativity in R&D organizations, this has been was greatly neglected. The current study adds value to the existing literature by deepening the authors’ understanding of the role of CHPWPs in enhancing resilience, the latter being a subject of huge focus of organizations during the pandemic.